Prevalence and Factors Associated with Burnout Syndrome in Nurses in Critical Care Units: A Systematic Review. - Aguilar Cabellos, Adita (2025)
Objective: To identify the prevalence of burnout syndrome in nurses working in critical care units, as well as the dimensions and associated factors that contribute to its development. Methods: Systematic review of articles published between 2014 and 2024, available in the databases ScienceDirect, Medline (PubMed), SciELO, Cochrane Library and Embase. The Descriptors in Health Sciences (DeCS) were used: nurse, nursing, critical care nursing, burnout and burnout syndrome, along with the Boolean operators AND and OR. The search strategy was structured using the acronym PICO and the PRISMA 2020 flowchart. After applying the inclusion and exclusion criteria, 28 original studies were selected. Main Results: The prevalence of burnout syndrome in nurses in critical units ranged from 31.1% to 53.6%. The most frequent dimension was emotional exhaustion, followed by depersonalization and low personal fulfillment. Among the associated internal factors, age, educational level, marital status and motherhood stand out; while, among the external factors, work overload, long working hours, emotional stress and lack of institutional support stand out. Overall Conclusion: Burnout syndrome constitutes a relevant occupational health problem in critical nursing units, with consequences that affect both the professional and the quality of care.